Comparison of unilateral versus bilateral intensity‐modulated radiotherapy for surgically treated squamous cell carcinoma of the palatine tonsil. Issue 23 (7th September 2017) - Chin, Re‐I; Rao, Yuan James; Hwang, Michael Y.; Spencer, Christopher R.; Pierro, Michael; DeWees, Todd; Patel, Pranav; Sinha, Parul; Gay, Hiram A.; Daly, Mackenzie; Haughey, Bruce H.; Nussenbaum, Brian; et al.
Abstract : BACKGROUND: The authors hypothesized that unilateral intensity‐modulated radiotherapy (IMRT) would decrease toxicity compared with bilateral IMRT for patients with lateralized palatine tonsillar cancer and a neck classification of N0 to N2b, with similar oncological outcomes. METHODS: A total of 154 patients were treated with postoperative IMRT from 1997 through 2013. Data were collected prospectively from 2005 to 2013 and retrospectively collected before 2005. Of those patients with lateralized primary and N0 to N2b disease, 48 received unilateral IMRT (group 1) and 59 received bilateral IMRT (group 2); a total of 47 patients had nonlateralized primary or N2c to N3 disease and received bilateral IMRT (group 3). RESULTS: The median follow‐up was 5.5 years. The 5‐year locoregional control rates were similar in group 1, group 2, and group 3 (100%, 96%, and 94%, respectively; pooled comparison: P  = .39 and group 1 vs group 2 comparison: P  = .19). The 5‐year overall survival rates were similar in group 1, group 2, and group 3 (85%, 79%, and 76%, respectively; pooled comparison: P  = .60 and group 1 vs group 2 comparison: P  = .25). There were no contralateral neck recurrences noted among unilaterally treated patients. Unilateral IMRT reduced acute toxicity and improved patient‐reported quality of life compared with bilateral IMRT. CONCLUSIONS: Unilateral IMRT appears to reduce acute toxicity and achieves oncological outcomes similar to those of bilateral IMRT in selected patients with lateralized palatine tonsillar cancer with a neck classification of N0 to N2b. Cancer 2017;123:4594‐4607 . © 2017 American Cancer Society . Abstract : There is controversy regarding whether patients with squamous cell carcinoma of the tonsil can be treated with unilateral neck radiotherapy. In the current study, unilateral intensity‐modulated radiotherapy appears to reduce acute toxicity and achieves oncological outcomes similar to those of bilateral intensity‐modulated radiotherapy in selected patients with lateralized palatine tonsil cancer with N0 to N2b disease.